Long-Term Nursing Home Entry: A Prognostic Model for Older Adults with a Family or Unpaid Caregiver - Wolff, Jennifer L. (J Am Geriatr Soc, 2018)
BACKGROUND/OBJECTIVES: We comprehensively examine factors associated with long-term nursing home entry across 6 domains of older adult and family caregiver risk from nationally representative surveys. We develop a prognostic model and a simple scoring system for use in risk stratification. DESIGN, SETTING, AND PARTICIPANTS: Our sample of 2676 community living older adults receiving help with self-care disability and their primary family/unpaid caregiver was drawn from the 1999 and 2004 National Long-Term Care Surveys and 2011 National Health and Aging Trends Study and linked caregiver surveys. MEASUREMENTS: Prediction of long-term nursing home entry (episodes >100 days or ending in death) by 24 months, ascertained from Minimum Data Set assessments and dates of death from Medicare enrollment files. Risk factors were measured from survey responses. RESULTS: In total, 16.1% of older adults entered a nursing home. Our final model and risk scoring system includes 7 independent risk factors: older adults’ age (1 point/5-years), living alone (5 points), dementia (3 points), 3–6 self-care activities (2 points), caregiver age (45–64 years: 1 point, 65–74 years: 2 points, 75+ years: 4 points), caregiver helps with money management (2 points), and caregiver reports moderate (2 points) or high (4 points) strain. Using this model, participants were assigned to risk quintiles. Long-term nursing home entry was 7.0% in the lowest quintile (0–6 points), 20.4% in the middle three quintiles (7–14 points), and 30.9% in the highest quintile (15–22 points). The model was well calibrated and demonstrated moderate discrimination with a c-statistic of 0.670 in the original data, 0.647 in bootstrapped samples, and 0.652 using the point-scoring system. CONCLUSIONS: We developed a prognostic model and simple scoring system that may be used to stratify community-living older adults by risk of long-term nursing home entry. Our model may be useful for population health and policy applications.